Fecal microbiota transplantation from female donors restores gut permeability and reduces liver injury and inflammation in middle-aged male mice exposed to alcohol - Lamas-Paz, Arantza; Mesquita, Mariana; Garcia-Lacarte, Marcos; Estévez-Vázquez, Olga; Benedé-Ubieto, Raquel; Gutierrez, Alejandro H.; Wu, Hanghang; Leal Lasalle, Hector; Vaquero, Javier; Bañares, Rafael; Martínez-Naves, Eduardo; Roa, Sergio; et al. (Frontiers in Nutrition, 2024)
Background: Alcohol misuse, binge drinking pattern, and gender-specific effects in the middle-aged population has been clearly underestimated. In the present study, we focused on understanding gender-specific effects of alcohol exposure on the gut-liver axis and the role of gut microbiota in modulating gender-specific responses to alcohol consumption.Methods: Fifty-two-week-old female and male C57BL/6 mice were fasted for 12 h, and then administered a single oral dose of ethanol (EtOH) [6g/kg]. Controls were given a single dose of PBS. Animals were sacrificed 8 h later. Alternatively, fecal microbiota transplantation (FMT) was performed in 52-week-old male mice from female donors of the same age. Permeability of the large intestine (colon), gut microbiota, liver injury, and inflammation was thoroughly evaluated in all groups.Results: Middle-aged male mice exposed to EtOH showed a significant increase in gut permeability in the large intestine, evaluated by FITC-dextran assay and ZO-1, OCCLUDIN and MUCIN-2 immuno-staining, compared to PBS-treated animals, whilst female mice of the same age also increased their gut permeability, but displayed a partially maintained intestinal barrier integrity. Moreover, there was a significant up-regulation of TLRs and markers of hepatocellular injury, cell death (AST, TUNEL-positive cells) and lipid accumulation (ORO) in male mice after EtOH exposure. Interestingly, FMT from female donors to male mice reduced gut leakiness, modified gut microbiota composition, ameliorated liver injury and inflammation, TLR activation and the senescence phenotype of middleaged mice.Our findings highlighted the relevance of gender in middle-aged individuals who are exposed to alcohol in the gut-liver axis. Moreover, our study revealed that gender-specific microbiota transplantation might be a plausible therapy in the management of alcohol-related disorders during ageing.